Mathematical Fluid Mechanics Advances in Convective Instabilities and Incompressible Fluid Flow - Aissa, A.; Aissa, A.; Ashoka, S. B.; Ashoka, S. B.; Chippar, Purushothama; Chippar, Purushothama; Joseph, T. V.; Joseph, T. V.; Kavitha, N.; Kavitha, N.; Lewis, Swaraj D.; Lewis, Swaraj D.; et al. (De Gruyter series on the applications of mathematics in engineering and information sciences, 2021)
This book aims to include various significant research topics of mathematical fluid mechanics having relevance or applications in engineering and applied sciences, covering the tools and techniques used for developing mathematical methods and modelling related to real-life situations.